Over-the-Counter Markets - Duffie, Darrell; Garleanu, Nicolae; Pedersen, Lasse Heje (Econometrica, 2005)
This chapter introduces the institutional setting of over-the-counter (OTC) markets and raises some of the key conceptual issues associated with market opaqueness. An OTC market does not use a centralized trading mechanism, such as an auction, specialist, or limit-order book, to aggregate bids and offers and to allocate trades. Instead, buyers and sellers negotiate terms privately, often in ignorance of the prices currently available from other potential counterparties and with limited knowledge of trades recently negotiated elsewhere in the market. OTC markets are thus said to be relatively opaque; investors are somewhat in the dark about the most attractive available terms and about whom to contact for attractive terms. Prices and allocations in OTC markets are, to varying extents, influenced by opaqueness and by the role of intermediating brokers and dealers.